Methods of Organizing the Process of Introducing Children to Subjects (Journal of Pedagogical Inventions and Practices, 2023)
In the world, introducing children to the environment and the outside world through visual activities, and for this purpose, the implementation of innovative teaching technologies that serve the comprehensive development of the individual in the preschool education system is a priority trend of global social development. Today, in developed countries, the spiritual and moral education of preschool children is recognized as one of the factors of the rise of human culture in determining the laws of all-round development of the personality by teaching visual activities. In the process of familiarization with the environment, and the development of personal qualities of preschool children, teaching creativity is gaining significant pedagogical importance on a global scale.